STUDY ON REGISTRATION AND RELEASE OF LOCAL VARIETIES OF CORN (Zea mays L.): KAJIAN PENDAFTARAN DAN PELEPASAN VARIETAS LOKAL TANAMAN JAGUNG (Zea mays L.) - Arisandi, Nadila (LPPM UPMI, 2023)
Corn (Zea mays L.) is one of the main food commodities after rice, and corn is a strategic commodity in agricultural development and driving the national economy [1]. Horticultural crop cultivation techniques in Indonesia, including maize, have different adaptability and depend on local conditions so that each region has morphological and physiological characteristics. This is evidenced by the release of the latest certified purple varieties from local varieties. Original varieties are plant varieties that have existed and been cultivated by farmers for generations, belong to the community and are controlled by the state. In Indonesia, germplasm is dominated by local varieties which play a role as a technological component in maintaining genetic, ecological and cultural diversity [3]. Indonesia as a constitutional state has various legal rules that form the basis of state and social life. One area of ​​law that is regulated is Intellectual Property Rights (IPR). Plant variety protection rights are commonly referred to as plant variety rights. The purpose of this research is to study PVP of corn plants to increase knowledge, especially in the development and protection of native varieties. This research method is a literature study. Literature study research is a research method that aims to analyze and evaluate existing literature. PVP is also carried out to encourage and provide opportunities for the business world to increase its role in various aspects of agricultural development. This is increasingly important considering that the compilation of superior cultivars in Indonesia is still mostly carried out by government research institutions.